Essentials of Interpretative Phenomenological Analysis - Smith, Jonathan A., author 293709; Nizza, Isabella E., author 656145; American Psychological Association (Online service) 655223 (Washington DC : American Psychological Association, 2021)
The brief, practical texts in the Essentials of Qualitative Methods series introduce social science and psychology researchers to key approaches to qualitative methods, offering exciting opportunities to gather in-depth qualitative data and to develop rich and useful findings. Essentials of Interpretative Phenomenological Analysis is a step-by-step guide to a research method that investigates how people make sense of their lived experience in the context of their personal and social worlds. It is especially well-suited to exploring experiences perceived as highly significant, such as major life and relationship changes, health challenges, and other emotion-laden events. Interpretative Phenomenological Analysis studies highlight convergence and divergence across participants, showing both the experiential themes that the participants share and the unique way each theme is manifested for the individual.